Ranking authors in academic social networks: a survey. Issue 1 (5th January 2018) - Amjad, Tehmina; Daud, Ali; Aljohani, Naif Radi
Abstract : Purpose: This study reviews the methods found in the literature for the ranking of authors, identifies the pros and cons of these methods, discusses and compares these methods. The purpose of this paper is to study is to find the challenges and future directions of ranking of academic objects, especially authors, for future researchers. Design/methodology/approach: This study reviews the methods found in the literature for the ranking of authors, classifies them into subcategories by studying and analyzing their way of achieving the objectives, discusses and compares them. The data sets used in the literature and the evaluation measures applicable in the domain are also presented. Findings: The survey identifies the challenges involved in the field of ranking of authors and future directions. Originality/value: To the best of the knowledge, this is the first survey that studies the author ranking problem in detail and classifies them according to their key functionalities, features and way of achieving the objective according to the requirement of the problem.